THE RELATIONSHIP OF AGE AND PARITY ON THE INCIDENT OF POSTPARTUM BLUESS IN PUBLIC WOMEN - Rika Ruspita; Komaria Susanti; Rifa Rahmi (Universitas Karya Husada Semarang, 2024)
The prevalence of postpartum blues varies throughout the world. Tanzania is 80% while in Japan it is 8%. The exact incidence of postpartum blues in Indonesia is not yet known, but several studies show that the incidence of postpartum blues is in the range of 50-70%. The aim of the research is to determine the relationship between age and parity on the incidence of postpartum blues among postpartum women at the Rosita Maternity Home in Pekanbaru. This research method uses quantitative methods through a correlative analytical design with a cross sectional approach. The research population was postpartum mothers at the Rosita Pekanbaru Maternity Home with a sample size of 30 respondents with a sampling technique using total sampling. Univariate and bivariate data analysis using the chi square statistical test. The results of the study based on univariate analysis showed that 66.6% of mothers experienced postpartum blues, 33.3% did not experience it, 60% of those aged at risk experienced postpartum blues, 40% of those who did not experience postpartum blues, 73% of primiparous mothers experienced postpartum blues. .3% who did not experience postpartum blues were 26.7%. The results of the bivariate analysis showed that there was a relationship between age and the incidence of postpartum blues with a P value of 0.045<0.05, there was no relationship between parity and the incidence of postpartum blues with a P value of 0.078>0.05. The conclusion is that there is a relationship between age and the incidence of postpartum blues, there is no relationship between parity and the incidence of postpartum blues, it is recommended that expectant mothers can prepare for pregnancy well so that it will prevent the incidence of postpartum blues, and for midwives to detect early the symptoms of postpartum blues so that they can also prevent its occurrence. postpartum blues